The electrical characteristics of a phthalocyanine heterojunction diode - Yakuphanoğlu, Fahrettin; Kandaz, Mehmet; Senkal, B. Filiz (Natl Inst Optoelectronics, 2009)
The electrical characteristics of nickel(II) phthalocyanine bearing 2'-aminophenylsulfanyl moieties/n-type silicon organic-on-inorganic semiconductor diode have been investigated by current-voltage characteristics. The diode indicates a good rectifying behavior. The ideality factor higher than unity of the diode is due to the interface states and series resistance. The ideality factor of the diode indicates that the NiPc appears to interact strongly with the Si inorganic semiconductor. The ideality factor n, barrier height Phi(b) and R-s values of the diode were determined and these electronic parameters vary with temperature. It is evaluated that at lower voltages, the current-voltage characteristics of the diode is controlled thermionic emission, whereas at higher voltages, the current of the diode is controlled by space charge injection limited mechanism.
Keywords: Organic/inorganic junction; Functional phthalocyanine